Specyfika zasady powszechności ochrony ubezpieczeniowej w ubezpieczeniu kredytu - Lisowski, Jacek (Credit insurance coverage availability specifics, 2006)
This article is focused on credit insurance coverage availability issues. This coverage needs to be reviewed under entity, subject and risk. Credit insurance is characterized by variety of entities, which can be insured, variety of subjects, which can be covered and specificity of credit risk, in particular marketable and non-marketable risks. This complexity is unique and important for this kind of insurance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 274-282